Scriem ecuația sub forma:
[tex]\it \sqrt{x+2+1+2\sqrt{x+2}} + \sqrt{x+2+4+4\sqrt{x+2}} = 5[/tex]
Notăm :
[tex]\it \sqrt{x+2} = y,\ y\ \textgreater \ 0, \ \Longrightarrow x+2 = y^2 [/tex]
Ecuația devine:
[tex]\it \sqrt{y^2+1+2y} +\sqrt{y^2 + 4+ 4y} =5 \Leftrightarrow \sqrt{(y+1)^2} +\sqrt{(y+ 2)^2} =5 [/tex]
[tex]\it \Leftrightarrow |y+1| + |y+2| = 5[/tex]
Deoarece y > 0, ecuația devine:
[tex]\it y+1+y+2 = 5 \Leftrightarrow y+y=5-1-2 \Leftrightarrow 2y = 2 \Leftrightarrow y =1 [/tex]
Acum, revenim asupra notației, și obținem:
[tex]\it \sqrt{x+2} =1 \Leftrightarrow x+2 = 1 \Leftrightarrow x = -1 .[/tex]